Kompetensi SDM Memoderasi Pengaruh Sistem Informasi Akuntansi terhadap Kualitas Laporan Keuangan UMKM - Aril, Muhammad; Nurul Aziza; Alvionita Lestari; Muhammad Ikram; Nurfadilah, Nurfadilah (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The purpose of this study is to determine how accounting information systems affect the quality of SME financial reports, with the potential moderating role of human resource capabilities. The approach used is a quantitative method, with a population of 14,819 SMEs in Palopo City, and samples collected using convenience sampling techniques, resulting in 38 responses. The data were evaluated using instrument testing, classical assumption testing, MRA testing, as well as coefficient of determination analysis and t-test with the help of SPSS version 26. The main findings indicate that accounting information systems do have a significant effect on the quality of SME financial statements, with a significance value of 0.000 < 0.05 and a t-value of 3.936 > the table t-value of 1.689. However, human resource capabilities are unable to moderate this effect, as the significance value reaches 0.423 > 0.05.